2014
DOI: 10.1016/j.celrep.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Escape from Telomere-Driven Crisis Is DNA Ligase III Dependent

Abstract: Short dysfunctional telomeres are capable of fusion, generating dicentric chromosomes and initiating breakage-fusion-bridge cycles. Cells that escape the ensuing cellular crisis exhibit large-scale genomic rearrangements that drive clonal evolution and malignant progression. We demonstrate that there is an absolute requirement for fully functional DNA ligase III (LIG3), but not ligase IV (LIG4), to facilitate the escape from a telomere-driven crisis. LIG3- and LIG4-dependent alternative (A) and classical (C) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 65 publications
11
105
0
Order By: Relevance
“…LIG3-mediated ligation is associated with microhomology usage, whereas the rapid kinetics of LIG4-mediated C-NHEJ generally preclude extensive processing and resection required for homology searching (Shibata et al 2011). Consistent with our published observations (Letsolo et al 2010;Jones et al 2014), we found that mean microhomology usage at inter-chromosomal junctions was greater for LIG4 −/− cells (2.38 nt) than LIG3 −/− cells (1.44 nt) ( Fig. 5A; Supplemental Fig.…”
Section: −/−supporting
confidence: 81%
See 4 more Smart Citations
“…LIG3-mediated ligation is associated with microhomology usage, whereas the rapid kinetics of LIG4-mediated C-NHEJ generally preclude extensive processing and resection required for homology searching (Shibata et al 2011). Consistent with our published observations (Letsolo et al 2010;Jones et al 2014), we found that mean microhomology usage at inter-chromosomal junctions was greater for LIG4 −/− cells (2.38 nt) than LIG3 −/− cells (1.44 nt) ( Fig. 5A; Supplemental Fig.…”
Section: −/−supporting
confidence: 81%
“…Physiologically, all lines experienced a 65%-83% reduction in cell number 48 h (t48) post-nucleofection (Supplemental Fig. 2E), consistent with an episode of mitotic arrest and telomere fusion akin to a telomeric crisis-state (Jones et al 2014). The WT populations recovered most rapidly, with a 10-fold increase in cell number between 48 and 120 h (t120), coincident with a threefold reduction in 17p fusion frequency (Fig.…”
Section: High Resolution Mapping Of Inter-and Intra-chromosomal Recommentioning
confidence: 85%
See 3 more Smart Citations